The Effect of the Use of Licorice Leaf Powder on the Productive Performance of Layers Chicken ISA Brown - Sameerah Hussein Amen; Ammar Qahtan Shanoon; Rashid Hassan Hamid; Esraa Kaiser Fares (Indian Journal of Forensic Medicine & Toxicology, 2021)
This study was conducted in the field of poultry for the Department of Livestock - Faculty of Agriculture -Kirkuk University for the period 10/14 until 2019/12/9 To find out the effect of different levels of glyyrrhizaglabra leaf powder on productive performance and some of the fascal qualities of blood and intestinalflora of white chicken. In this experiment In this experiment, 28 chickens at the age of 24 weeks wereused., randomly distributed to the cages with five treatments and a rate of two repeaters per treatments(2b/treatments), the first treatments (control) diet without any addition while the second, third, fourth andfifth treatment was taken on a scent edited by Glyyrrhiza glabra 0.25, 0.5.0.75, 0.1% respectively, Theexperiment period of 56 days was divided into three equal periods (14 days/ period). I has shown in theproductive qualities produced in the rate of egg production in the first period significant different the third,fourth and fifth treatments and in the general rate significant different the fourth and fifth treatments In theaverage weight of the eggs, there were no significant differences between the treatments. We note in theegg mass rate in the second period the fifth treatments significant different on the other treatments. At thegeneral rate, the treatment fourth and fifth on the other treatments In the rate of feed consumption shows asignificant different in the first and second periods and the general rate in the fourth and fifth treatments onthe other treatments and in the third periods significant different the fifth treatments In the food conversion.